2010
DOI: 10.1677/joe-10-0341
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with GH, insulin, and indomethacin alleviates cancer cachexia in a mouse model

Abstract: Cancer-induced cachexia involves weight loss, catabolic activity, and inflammation. We have evaluated the effects of various treatments (GH, insulin (INS), indomethacin (IND), and all possible combinations) on cancer cachexia in a mouse model. BALB/c mice that were implanted with colon-26 adenocarcinoma developed cachexia in 9 days. Body weight, tumor volume, tumor-free weight, inflammatory cytokines (tumor necrosis factor-a (TNF-a), interleukin 6 (IL6)), and nutritional markers (glucose (Glu), albumin, trigly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Anesthetized rats were subcutaneously inoculated with either 1 ϫ 10 6 -10 7 cells/site (tumor-bearing rats) or saline alone (non-tumorbearing control rats) in the left and right flanks. The major and minor tumor axes were measured, and the tumor volume was estimated using the following equation: tumor volume (cm 3 ) ϭ major axis (cm) ϫ minor axis (cm) ϫ minor axis (cm) ϫ 1/2, and tumor volume was converted to tumor weight (mg)/mm 3 (14,17,66). Rat model characterization.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Anesthetized rats were subcutaneously inoculated with either 1 ϫ 10 6 -10 7 cells/site (tumor-bearing rats) or saline alone (non-tumorbearing control rats) in the left and right flanks. The major and minor tumor axes were measured, and the tumor volume was estimated using the following equation: tumor volume (cm 3 ) ϭ major axis (cm) ϫ minor axis (cm) ϫ minor axis (cm) ϫ 1/2, and tumor volume was converted to tumor weight (mg)/mm 3 (14,17,66). Rat model characterization.…”
Section: Methodsmentioning
confidence: 99%
“…Although cachexia strongly impacts the success of therapeutic treatments, the mechanisms underlying this syndrome are not fully understood. Stomach cancer patients in particular have the highest incidence of cachexia; however, few experimental models for the study of stomach cancer cachexia have been established (4,14,66).A useful cachexia model must meet three of the following five diagnostic criteria in addition to weight loss: anorexia, decreased muscle strength, fatigue, low fat-free mass (FFM) index, and abnormal biochemistry (anemia, increased inflammatory markers, and low serum albumin) (14). Moreover, Argilés et al (1) reported that two specific indicators, anorexia and metabolic disturbances, should be identified before arriving at a diagnosis of cachexia-associated weight loss.…”
mentioning
confidence: 99%
See 3 more Smart Citations